Search for flavor changing neutral currents in top quark decays in pp collisions at 7 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Aguilo, E; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; et al. (2013)
The results of a search for flavor changing neutral currents in top quark decays t→Zq in events with a topology compatible with the decay chain tt̄→Wb+Zq→ℓνb+ℓℓq are presented. The search is performed with a data sample corresponding to an integrated luminosity of 5.0 fb-1 of proton-proton collisions at a center-of-mass energy of 7 TeV, collected with the CMS detector at the LHC. The observed number of events agrees with the standard model prediction and no evidence for flavor changing neutral currents in top quark decays is found. A t→Zq branching fraction greater than 0.21% is excluded at the 95% confidence level. © 2012 CERN.